From Molecular Design to Co-sensitization; High performance indole based photosensitizers for dye-sensitized solar cells. (20th April 2016) - Babu, Dickson D.; Su, Rui; El-Shafei, Ahmed; Adhikari, Airody Vasudeva
Graphical abstract: Highlights: First report on the effect of anchoring groups on co-sensitization performance. Two novel co-adsorbers have been designed and synthesized. Barbituric acid has emerged as a good anchoring group for co-sensitizers. Co-sensitized device displayed an enhanced efficiency of 8.06%. Abstract: Herein, we report the molecular design and synthesis of two novel organic co-adsorbersDBA-1 ((Z)-2-cyano-3-(5-(4-(cyclohexa-1, 5-dien-3-ynyl(phenyl)amino)phenyl)-1-hexyl-1H-indol-3-yl)acrylic acid) and(DBA-2 ) 5-((5-(4-(diphenylamino)phenyl)-1-hexyl-1 H -indol-3-yl)methylene)pyrimidine-2, 4, 6(1 H, 3 H, 5 H )-trione with D-D-A (donor-donor-acceptor) architecture. We have combined the strong electron donating triphenylamine group with indole moiety attached to different acceptors/anchoring groups, as co-adsorbers for dye-sensitized solar cells and we present for the first time, the role of anchoring/acceptor unit on their co-adsorption properties. In this study, cyanoacetic acid and barbituric acid are employed as anchoring groups in the co-sensitizersDBA-1 andDBA-2, respectively. Their electrochemical and photo-physical properties along with molecular geometries, obtained from Density Functional Theory (DFT) are employed to vindicate the effect of co-sensitizer structures on photovoltaic properties of DSSCs. We have demonstrated that the co-sensitization effect is profoundly dependent upon the anchoring/acceptor unit in the co-adsorber molecule. Devices co-sensitized usingDBA-1 andDBA-2 along withHD-2 ( Ru-complex of 4, 4'-bis-(1, 4-benzodioxan-5-yl-vinyl)-[2, 2']bipyridine), displayed higher power conversion efficiencies (PCEs) than the device sensitized using onlyHD-2 . In the present work, ruthenium based sensitizer, HD-2, has been chosen due to its better solar-to-power conversion efficiency and impressively higher photocurrent densities than that of standardN719 . Among them, co-adsorberDBA-2, containing barbituric acid as the acceptor/anchoring group displays promising photovoltaic results and exhibited an enhanced efficiency of 8.06%. Further, good agreement between the calculated and experimental results showcase the precision of the energy functional and basis set utilized in this study. All these findings provide a deeper insight and better understanding into the intricacies involved in the design of superior co-sensitizers for development of highly efficient DSSCs.